Performing under pressure : gaining the mental edge in business and sport - Miller, Saul L. (J. Wiley & Sons Canada, 2010)
"Performing Under Pressure is for anyone interested in insights and techniques that will help them to succeed ... and do so with more ease. The book is filled with a variety of engaging and illustrative examples and a training program to master the elements of performing under pressure"--Resource description page.